Modulation of pacemaker channel function in a model of thalamocortical hyperexcitability by demyelination and cytokines. (25th January 2022) - Chaudhary, Rahul; Albrecht, Stefanie; Datunashvili, Maia; Cerina, Manuela; Lüttjohann, Annika; Han, Ye; Narayanan, Venu; Chetkovich, Dane M; Ruck, Tobias; Kuhlmann, Tanja; Pape, Hans-Christian; Meuth, Sven G; et al.
Abstract: A consensus is yet to be reached regarding the exact prevalence of epileptic seizures or epilepsy in multiple sclerosis (MS). In addition, the underlying pathophysiological basis of the reciprocal interaction among neuroinflammation, demyelination, and epilepsy remains unclear. Therefore, a better understanding of cellular and network mechanisms linking these pathologies is needed. Cuprizone-induced general demyelination in rodents is a valuable model for studying MS pathologies. Here, we studied the relationship among epileptic activity, loss of myelin, and pro-inflammatory cytokines by inducing acute, generalized demyelination in a genetic mouse model of human absence epilepsy, C3H/HeJ mice. Both cellular and network mechanisms were studied using in vivo and in vitro electrophysiological techniques. We found that acute, generalized demyelination in C3H/HeJ mice resulted in a lower number of spike–wave discharges, increased cortical theta oscillations, and reduction of slow rhythmic intrathalamic burst activity. In addition, generalized demyelination resulted in a significant reduction in the amplitude of the hyperpolarization-activated inward current ( I h ) in thalamic relay cells, which was accompanied by lower surface expression of hyperpolarization-activated, cyclic nucleotide-gated channels, and the phosphorylated form of TRIP8b (pS237-TRIP8b). We suggest that demyelination-related changes in thalamic I h may be one of the factors defining the prevalence of seizures in MS.